2011
DOI: 10.1371/journal.pone.0029466
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Mediated Upregulation of Noxa Is Associated with Cell Cycle Progression in Estrogen Receptor-Positive Breast Cancer Cells

Abstract: Noxa is a Bcl-2-homology domain (BH3)-only protein reported to be a proapoptotic member of the Bcl-2 family. Estrogen has been well documented to stimulate cell growth and inhibit apoptosis in estrogen receptor (ER)-positive breast cancer cells. Intriguingly, recent reports have shown that 17β-estradiol (E2) induces Noxa expression, although the mechanisms underlying E2-mediated induction of Noxa and its functional significance are unknown. Using MCF7 human breast cancer cells as an experimental model, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
(59 reference statements)
0
21
0
Order By: Relevance
“…However, it has been shown that in different cellular systems the up-regulation of Noxa at both protein and mRNA level induced by bortezomib can also occur through p53-independent mechanisms [22], [34], [37], [38], such as myc transcriptional regulation [24]. Indeed, it was demonstrated that c-Myc can bind the Noxa promoter and regulate its transcription [24], [39]. As shown in Figure 6, Noxa overexpression occurs in REN cells upon treatment with bortezomib.…”
Section: Discussionmentioning
confidence: 98%
“…However, it has been shown that in different cellular systems the up-regulation of Noxa at both protein and mRNA level induced by bortezomib can also occur through p53-independent mechanisms [22], [34], [37], [38], such as myc transcriptional regulation [24]. Indeed, it was demonstrated that c-Myc can bind the Noxa promoter and regulate its transcription [24], [39]. As shown in Figure 6, Noxa overexpression occurs in REN cells upon treatment with bortezomib.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we showed that NOXA expression in MRT cell lines inhibited growth as efficiently as hSNF5 reexpression. Although several reports have shown NOXA as a positive growth regulator, taken together, these data implicate NOXA expression as a contributor to the strong growth inhibition induced by hSNF5 reexpression (34, 35). Alternately, hSNF5 loss may result in a failure to regulate NOXA expression in the case of DNA damage by some chemotherapy agents such as doxorubicin.…”
Section: Discussionmentioning
confidence: 74%
“…While NOXA is well known for its role as a pro‐apoptotic member of the BCL‐2 family, it has become increasingly evident that NOXA plays important roles in other cellular processes. NOXA expression is upregulated upon estrogen stimulation and is required for cell cycle progression in estrogen receptor‐positive breast cancer cells [26]. NOXA has also been shown to promote cell growth by stimulating glucose consumption via the pentose phosphate pathway [27].…”
Section: Discussionmentioning
confidence: 99%